Association of sera levels of anti‐pemphigoid autoantibody (BP 180) with AD: A pilot case‐control study: Developing topics. (7th December 2020) - Salama, Mohamed; Shalash, Ali
Abstract: Background: Bullous pemphigoid (BP) is a common dermatological disease affecting the aging population. Previous research showed potential cross‐talks between BP patients and those with neurodegenerative diseases e.g. dementia. The present study assessed serum levels of autoantibodies (AIAs) against pemphigoid in a sample of Alzheimer's disease (AD) as well as Parkinson's disease (PD) patients compared to matched healthy controls. Method: Twenty‐five PD patients were compared to fifteen AD patients and matched ten controls. All patients were evaluated clinically and their sera were collected to estimate levels of AIAs against pemphigoid. PD stages were considered clinically using UPDRS subscales, Hoehn and Yahr scale, and Schwab and England scales, while AD patients were evaluated using MoCA scale. Result: The results showed a significant elevation in BP 180 AIAs in AD patients (37.5%) compared to PD patients (14%) and controls (10%). Conclusion: The present findings highlight the possible role of cross‐reactivity between the skin and brain antigens in developing AD.